Optimization of Water Management for Green Pepper Production in a Water-Limiting Tropical Savanna Agroecological Zone Based on Crop Water Productivity - Rose Alegewe; Abdul-Ganiyu Shaibu; Yakubu Saaka Zakaria (Journal of Engineering)
This study aimed to determine the optimum levels of irrigation regime and irrigation schedule based on crop water productivity for the sustainable production of green pepper in a water-limiting tropical savannah agroecological zone. The study was conducted at the Hydro Farm of MotorKing Company Limited in the Tamale Metropolis, Northern Region, Ghana. The experimental design was a 2 × 3 factorial experiment laid out in a randomized complete block and replicated five times. Irrigation schedule at two levels (one-time daily application and split daily application at 60% morning and 40% evening) and irrigation regime at three levels (100% ETc, 80% ETc, and 60% ETc) were the factors. The “Yolo Wonder” variety of green pepper was the test crop. The crop was planted at a planting distance of 0.3 m within rows and 0.5 m between rows. Treatments were applied using a drip irrigation system. Crop water requirements (ETc) of green pepper were estimated using the CROPWAT model. Crop yield and water applied under each treatment were determined. Crop yield was measured at harvest as the total weight of fruits per hectare. Crop water productivity was determined under each treatment as crop yield per unit of water consumed. Data analysis was done in Genstat (12th edition). Analysis of variance (ANOVA) and Duncan’s multiple range test at 5% level of significance were employed to separate differences in treatment means. The results suggest that both irrigation regime and irrigation schedule have significant influence on the yield and crop water productivity of green pepper. Irrigating at 60% ETc and split irrigation (60% morning and 40% evening) gave significantly higher yields and crop water productivity compared to the other levels of the factors. This study demonstrated that irrigation schedule and irrigation regime are important factors to consider in the optimization of water management for green pepper; however, further research is needed to identify the optimal levels of these factors and the most effective irrigation strategies for the crop in different environments.